Estudio de factibilidad para la creación de un centro rural de esparcimiento canino en lo referente a guardería “Pet Lover” en Manizales (Col) (2014)
Pet Lover gathers the dogs’ fans and owners’ feelings regarding the dog’s care and entertainment. It will cover the owners’ needs when they cannot take care of their dogs by providing them with a countryside place, where their dogs can be in contact with nature at an affordable price. Dogs would be picked up and left at the door of the owner and they will, of course, be properly bathed. It should be noted that the facility must not be far away from the city, since it is important to have a facility with an easy and quick access. It means a countryside place located 20 or 30 minutes away from the city. It also provides a hotel and dog daycare service as an entertainment and quietness for the best man’s friend, !the dog!. The investment of the partners is estimated to be 14, 55% as total initial investment that projects a 5 year IRR of 19, 1%. This makes it a highly attractive investment because it has a cost benefit of 1,19 vs. the market opportunities under the same conditions. This projection is based on the net present value of the 5 year Gross Profit of COP $13.872.881. The company will be created as a Simplified Stock Company, where the partitions of the partners as well as the duties and responsibilities will be equal.